Strategi Promosi dan Inovasi Produk Upaya Memulihkan dan Meningkatkan UMKM Masyarakat di Desa Kopen - Anissa Widiyastuti; Nur Tanfidiyah (Transformatif : Jurnal Pengabdian Masyarakat, 2021)
This service activity focuses on Micro, Small and Medium Enterprises (MSMEs) in Kopen Village, Ngadirejo Village, Kartasura District so that what will be discussed in depth is economic activity in the form of production. The purpose of this service is to carry out promotional strategies through social media and product innovation to prevent boredom and encourage consumer appeal. While the service method used is Participatory Action Research. This method has several stages that must be carried out, including: 1) assessing needs, 2) designing needs, 3) implementing planning, and 4) evaluating the activities that have been carried out. While the results of these activities, the community really appreciates it. Because promotional strategy activities and product innovation provide new insights, especially on the use of technology to promote their merchandise more easily anywhere and anytime. Most of the participants asked to join the culinary group on social media, one of which was Facebook. In addition, product innovation makes merchandise more attractive and different. This was proven after several days of UMKM participants posting their products on social media, some of the participants got responses from the public starting from asking for merchandise. Based on the statements and results made, it is sufficient to confirm that the existence of promotional strategies and product innovation activities helps restore and improve community businesses in Kopen village.